Financial Distress dan Kompleksitas Operasi pada Waktu Publikasi Laporan Keuangan dengan Reputasi KAP sebagai Pemoderasi - Wirantini, Putu Isma Suyanti; Rasmini, Ni Ketut (E-Jurnal Akuntansi, 2024)
This research aims to examine the influence of financial distress and operational complexity on the time of publication of financial reports with the KAP's reputation as a moderator. This research was conducted at consumer cyclicals sector companies listed on the Indonesia Stock Exchange in 2020-2021. The number of observation objects was 148 which were selected using the purposive sampling method. The data analysis technique used is Moderated Regression Analysis (MRA) which shows the results that financial distress has a positive effect on the time of publication of financial reports, operational complexity has no effect on the time of publication of financial reports, the KAP's reputation is unable to moderate the influence of financial distress and operational complexity at the time of publication. financial statements. Keywords:Financial Distress; Operational Complexity; Public Accounting Firm Reputation; Publication Time of Financial Statements